PROBIOTICS FROM ARTEMIA AND ITS APPLICATION ON CONTROLLING THE BACTERIAL PATHOGENS IN AQUACULTURE SYSTEM - SARASWATHI MOHAN S.; BIPIN KUMAR JHA; AJITHA MOL A.; MICHAEL BABU M. (International Journal of Pharma and Bio Sciences, 2014)
The present work was conducted to isolate the gut bacteria of Artemia and to use them as probiotics to control the bacterial pathogens in aquaculture systems. In the present study, two of bacterial species were isolated from the gut of Artemia which was collected from Puthalam saltpan (Kanyakumari, India). Among the gut isolates of Artemia, best two species, Alteromonas sp. and Acetobacterium sp. were selected. These two isolates were tested for its efficiency and antagonistic activity against Vibrio harveyi and Alteromonas sp. Artemia gut isolates, when introduced in to the gut of adult Artemia along with pathogenic bacteria, they multiplied and colonized faster and seen in higher number than the pathogenic bacteria . During the present study it was found that Acetobacterium sp. effectively controlled the growth of V. harveyi and Alteromonas sp. than Aeromonas sp. Hence this study adds more towards the use of gut isolates of Artemia as probiotics and on controlling the bacterial pathogens in an aquaculture system to solve the bacterial Pathogenicity.